PENGARUH TARIF PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR SAMSAT KOTA SALATIGA - Juriyanto; Edwin Zusrony; Agustinus Budi Santoso (LPPM Universitas Sains Dan Teknologi Komputer, 2025)
This research aims to test the variables of tax rates and tax sanctions on motor vehicle taxpayer compliance at SAMSAT Salatiga City, Central Java. The population in this research is motor vehicle taxpayers who are currently paying vehicle tax at SAMSAT Salatiga City. The sample consisted of 60 respondents taken using a non-random sampling method with a purposive sampling technique. Data collection used a questionnaire with a five-point Likert scale parameter as primary data. Data analysis in this research used the multiple linear regression method and was processed using Predictive Analytics SoftWare, namely SPSS 29. The results of multiple regression testing showed that the variables of tax rates and tax sanctions had a significant positive effect on motor vehicle taxpayer compliance. The results of simultaneous testing also showed that the variables of tax rates and tax sanctions had a significant positive effect on motor vehicle taxpayer compliance.